The women and girls associated with Boko Haram: How has the Nigerian government responded?. Issue 2 (3rd April 2021) - Botha, Sven
ABSTRACT: Following the Chibok abductions of April 2014, the involvement of women and girls in the Boko Haram insurgency has increased, as has the subsequent analysis of them in both the academic and the grey literature. Contributions have mainly focused on how women and girls have been incorporated into – or used by – Boko Haram. In contrast, this article focuses on the response of the Nigerian government to the plight of women and girls that have become associated with Boko Haram. A qualitative analysis consisting of desktop research, consultation of policy documents and first hand interviews informed the research. The article finds that while the Nigerian government has taken note of the plight of these women and girls, it appears mostly an afterthought. Additionally, policy responses have not taken the full cycle of female participation in terrorist activity with Boko Haram into account. Recommendations to address this gap are offered.